2019
DOI: 10.3174/ajnr.a6317
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment and Reporting Quality of Intracranial Vessel Wall MR Imaging Studies: A Systematic Review

Abstract: BACKGROUND: Over the last quarter-century, the number of publications using vessel wall MR imaging has increased. Although many narrative reviews offer insight into technique and diagnostic applications, a systematic review of publication trends and reporting quality has not been conducted to identify unmet needs and future directions. PURPOSE: We aimed to identify which intracranial vasculopathies need more data and to highlight areas of strengths and weaknesses in reporting. DATA SOURCES: PubMed, EMBASE, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 67 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…Many pilot studies have demonstrated its complementary values for the diagnosis of intracranial dissection over DSA, magnetic resonance angiography (MRA) and computed tomography angiography (CTA) by harnessing its excellent soft tissue contrast [ 3 , 9 11 ]. However, compared with carotid atherosclerosis, investigations on the diagnostic utility of hrCMR are much less commonly performed with intracranial vasculopathies including dissections [ 12 ]. It has been suggested that hrCMR should be used as a second-line diagnostic modality when there is diagnostic uncertainty [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many pilot studies have demonstrated its complementary values for the diagnosis of intracranial dissection over DSA, magnetic resonance angiography (MRA) and computed tomography angiography (CTA) by harnessing its excellent soft tissue contrast [ 3 , 9 11 ]. However, compared with carotid atherosclerosis, investigations on the diagnostic utility of hrCMR are much less commonly performed with intracranial vasculopathies including dissections [ 12 ]. It has been suggested that hrCMR should be used as a second-line diagnostic modality when there is diagnostic uncertainty [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of studies utilizing VWI of intracranial vessels has increased exponentially since the first report describing VWI in 1994. About half of these studies are related to atherosclerotic lesions, but the number of studies on aneurysms is also increasing [7] . In particular, in patients with multiple cerebral aneurysms, VWI with contrast-enhanced MRI is useful in identifying the specific aneurysm that has ruptured based on the contrast enhancement of the aneurysm wall [4 , 8] .…”
Section: Discussionmentioning
confidence: 99%
“…2 Because this sequence is intended mainly for evaluation of wall features, suppression of cerebrospinal fluid (CSF) is important. [3][4][5] Here, we employed T2-weighted images, in which the contrast between the low-intensity flow void of the vessels and the high-intensity CSF permits vessel identification without contrast medium. To our best knowledge, this is the first report to demonstrate the feasibility of T2-SPACE for imaging of occluded vessels.…”
Section: Discussionmentioning
confidence: 99%